Induction of polyploid tillered onion using colchicine and pendimethalin - Ren, Jian; Wu, Xiaoxu; Song, Ce; Yu Liang, Yu; Gao, Wenzheng; Wang, Yong (Penebit Universiti Kebangsaan Malaysia, 2018)
The shoot tip explants of the tillered onion line Z-018 were used as experimental materials. The effects of colchicine and pendimethalin on the induction of polyploid tillered onion were studied in vitro with different concentrations and treatment time. Treatment with 250 μmol/L colchicine for 4 days caused a variant rate of 42.22% and a mortality rate of 36.67%, whereas treatment with 30 μmol/L pendimethalin for 6 days caused a variant rate of 41.11% and a mortality rate of 24.44%. Subsequent cytological identification showed that tetraploid plants were successfully induced by both mutagens. Compared with the diploid plants, the tetraploid plants exhibited slower growth, thicker leaves, stems and roots, larger stomatal apparatus and increased number of chloroplasts. In addition, the obtained tetraploid plants have thicker tubular leaves, decreased number of tillers, larger bulbs and increased yield of the products. This provides the basis for future research on tillered onion germplasm resources.